Transinhibition of C1 inhibitor synthesis in type I hereditary angioneurotic edema. - Kramer, J (1993)
To ascertain the mechanism for decreased synthesis of C1 inhibitor (C1 INH) in certain patients with the autosomal dominant disorder hereditary angioneurotic edema, we studied expression of C1 INH in fibroblasts in which the mutant and wild type mRNA and protein could be distinguished because of deletion of exon 7 (delta Ex7). In the HANE delta Ex7 cells, the amount of wild type mRNA (2.1 kb) was expressed at 52 +/- 2% (n = 5) of normal, whereas the mutant mRNA was 17 +/- 1% (n = 5) of normal. Rates of synthesis of both wild type and mutant proteins (11 +/- 3 and 3 +/- 1% of normal, respectively) were lower than predicted from the mRNA levels. There was no evidence of increased C1 INH protein catabolism. These data indicate that there are multiple levels of control of C1 INH synthesis in type I hereditary angioneurotic edema. Pretranslational regulation results in < 50% of the mutant truncated 1.9-kb mRNA. In addition, translational regulation results in decreased synthesis of both wild type and mutatn C1 INH proteins. These data suggest a transinhibition of wild type C1 INH translation by mutant mRNA and/or protein.